2021
DOI: 10.1002/jmv.27133
|View full text |Cite
|
Sign up to set email alerts
|

In‐hospital mortality in SARS‐CoV‐2 stratified by serum 25‐hydroxy‐vitamin D levels: A retrospective study

Abstract: This study is done to estimаte in‐hоsрitаl mоrtаlity in раtients with severe асute resрirаtоry syndrоme соrоnаvirus 2 (SАRS‐СоV‐2) strаtified by Vitamin‐D (Vit‐D) levels. Раtients were strаtified ассоrding tо by serum 25‐hydroxy‐vitamin D (25(OH)Vit‐D) levels intо twо grоuрs, that is, 25(OH)Vit‐D less thаn 40 nmol/L аnd 25(OH)Vit‐D greаter thаn 40 nmol/L. А tоtаl оf 231 раtients were inсluded. Оf these, 120 (50.2%) оf the раtients hаd 25(OH)Vit‐D levels greаter thаn 40 nmol/L. The meаn аge wаs 49 ± 17 yeаrs, а… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…The study was conducted between February 26, 2020 and September 8, 2020. The data were collected from the electronic medical records of two hospitals in Kuwait: Jaber Al-Ahmed Hospital and Al Adan General Hospital [ 17 , 18 , 19 ]. During the data entry stage, an electronic case report form was used.…”
Section: Methodsmentioning
confidence: 99%
“…The study was conducted between February 26, 2020 and September 8, 2020. The data were collected from the electronic medical records of two hospitals in Kuwait: Jaber Al-Ahmed Hospital and Al Adan General Hospital [ 17 , 18 , 19 ]. During the data entry stage, an electronic case report form was used.…”
Section: Methodsmentioning
confidence: 99%
“…The results of a pilot study in Spain suggest that vitamin D supplementation may reduce disease severity 52 . In contrast, a retrospective cohort study of 231 patients found that serum calcidiol levels were not significant in predicting mortality in patients with SARS-CoV-2 37 . Another cohort study suggested a similar risk of mortality in COVID-19, independent of vitamin D concentration 38 .…”
Section: Discussionmentioning
confidence: 85%
“…All the data were obtained from electronic medical records from two tertiary care hospitals in Kuwait: Jaber Al‐Ahmed Hospital and Al Adan General Hospital. 11 , 12 , 13 An electronic case‐record form (CRF) was used for data entry.…”
Section: Methodsmentioning
confidence: 99%